Properties of HI discs in the Auriga cosmological simulations - Marinacci, Federico; Grand, Robert J. J.; Pakmor, Rüdiger; Springel, Volker; Gómez, Facundo A.; Frenk, Carlos; White, Simon D. M. (Arxiv, 2017)
We analyse the properties of the HI gas distribution in the Auriga project, a set of magnetohydrodynamic cosmological simulations performed with the moving-mesh code AREPO and a physics model for galaxy formation that succeeds in forming realistic late-type galaxies in the 30 Milky Way-sized haloes simulated in this project. We use a simple approach to estimate the neutral hydrogen fraction in our simulation set, which treats low-density and star-forming gas separately, and we explore two different prescriptions to subtract the contribution of molecular hydrogen from the total HI content. The HI gas in the vast majority of the systems forms extended discs although more disturbed morphologies are present. Notwithstanding the general good agreement with observed HI properties -- such as radial profiles and the mass-diameter relation -- the Auriga galaxies are systematically larger and more gas-rich than typical nearby galaxies. Interestingly, the amount of HI gas outside the disc plane correlates with the star formation rate, consistent with a picture where most of this extra-planar HI gas originates from a fountain-like flow. Our findings are robust with respect to the different assumptions adopted for computing the molecular hydrogen fraction and do not vary significantly over a wide range of numerical resolution. The HI modelling introduced in this paper can be used in future work to build artificial interferometric HI data cubes, allowing an even closer comparison of the gas dynamics in simulated galaxies with observations.